Reconstruction of the Obliterated Eustachian Tube: A Pilot Case Series - Toivonen Joonas; Poe Dennis (WILEY, 2022)
Objective: To investigate the safety and early efficacy of a procedure for reconstruction of the obliterated Eustachian tube (ET).
Study design: Retrospective case series.
Methods: Patients with total obliteration of the cartilaginous ET, with intractable mucoid effusion causing repeated occlusion of tympanostomy tubes were included. Patients underwent endoscopic transnasal/transoral reconstruction of the obliterated ET using transtympanic illuminated guidewire guidance. A temporary stent (angiocatheter filled with bonewax) was placed to maintain patency while healing. In four cases an additional steroid-eluting propel stent was placed in the ET orifice. Main outcome measures were otomicroscopy results, absence of middle ear effusion, and nasopharyngoscopy showing patency of the ET orifice.
Results: Nine ETs (seven patients), ages 17-68 years (mean 37.9) underwent ET reconstruction. Follow-up ranged from 4 to 56 months (mean 30.9 months). 89% of operated ears had no effusion at last follow-up. Two patients (three Eustachian tubes) underwent successful reoperation. There were no complications directly related to the procedure. Etiologies of obliteration included scarring after sinus surgery, obstruction after maxillo-mandibular advancement surgery (two patients), bullous pemphigus, gunshot trauma, and previous patulous obliteration (two patients).
Conclusions: Complete occlusion of the cartilaginous ET can be associated with intractable mucoid effusion; endoscopic examination should be considered in such cases. In this pilot study, ET reconstruction was found to be a safe and possibly effective procedure in patients with total obliteration of the ET from various etiologies. Larger studies with long term follow up are indicated.
Level of evidence: 4 Laryngoscope, 2022.